2017
DOI: 10.1007/s00429-017-1442-y
|View full text |Cite|
|
Sign up to set email alerts
|

Increased glutamic acid decarboxylase expression in the hypothalamic suprachiasmatic nucleus in depression

Abstract: In depression, disrupted circadian rhythms reflect abnormalities in the central circadian pacemaker, the hypothalamic suprachiasmatic nucleus (SCN). Although many SCN neurons are said to be GABAergic, it was not yet known whether and how SCN GABA changes occur in the SCN in depression. We, therefore, studied GABA in the SCN in relation to the changes in arginine vasopressin (AVP), which is one of the major SCN output systems. Postmortem hypothalamus specimens of 13 subjects suffering from depression and of 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
(69 reference statements)
2
19
0
Order By: Relevance
“…After 5 days in culture, we still detected many viable cells either in slices treated with medium only or medium plus ethanol (Figure ) as we have found in previous studies .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…After 5 days in culture, we still detected many viable cells either in slices treated with medium only or medium plus ethanol (Figure ) as we have found in previous studies .…”
Section: Resultssupporting
confidence: 88%
“…To address this putative relationship between CYP17A1 and TrkB we treated post‐mortem human brain slices in short‐term cultures with DHEA (a major product of CYP17A1) or DHEAS. The use of post‐mortem human brain slice cultures was pioneered by our group and it has been established that many cells in the cultured slices remain viable for long periods in vitro . Here, we show that treatment with DHEA increases BDNF mRNA levels in the human brain slices, compared to vehicle‐treated slices.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Of note, some studies have suggested a gender difference in plasma AVP levels, despite a lack of consistent findings across all studies. Wu et al reported a significant 253% increase of AVP-ir in female depressed subjects but not in male depressed patients [19]. One study found male controls to have higher peripheral AVP levels compared to female controls, suggesting a possible relationship between sex hormones and AVP [17].…”
Section: Avp and Gendermentioning
confidence: 98%
“…There is conflicting evidence as to whether the SCN directly modulates mood and anxiety. Several human postmortem brain studies find alterations in specific neurotransmitters and/or receptors in the SCN of individuals with a mood disorder [22][23][24] .…”
Section: Suprachiasmatic Nucleus Regulates Anxiety Behaviormentioning
confidence: 99%